IMPORTANCE OF BODY SYMMETRY TO ESTABLISH STAND BALANCE AFTER DROP JUMP - Ana Kašček Bučinel; Matej Supej; Nicola Petrone; Ivan Čuk (University of Ljubljana Press (Založba Univerze v Ljubljani), 2024)
The aim of the study was to determine if body symmetry influences establishing stand balance after drop jump.  Thirty-two healthy sports students participated in this study, with an average age 19.8 ± 1.4 years, height of 182.9 ± 6.8 cm and weight of 79.1 ± 8.1 kg. Morphological characteristics were assessed by measuring the differences between the left and right side of forearm girth, upper arm girth, calf girth, thigh girth, long shoulder height, lean mass of legs and lean mass of arms. The standing balance result was calculated based on factor scores obtained from nine measurements taken for 30 seconds after jumping from a 25 cm height platform. These measurements included three for normal stand, three for blind stand, and three for deaf stand. The data was collected using a pressure insoles system and by measuring the difference in ground reaction force between the left and right leg. Regression analysis revealed that 27% of the differences in leg load could be explained by differences in morphological characteristics between the left and right side. Two significant predictors were identified: the difference in long shoulder height (explaining 16% of the variance) and the differences in arm lean mass (explaining 11% of the variance). Both variables showed a negative relationship with the factor jump standing. It was observed that imbalances in body symmetry could increase the long-term risk of acute or chronic injuries.